2021
DOI: 10.1101/2021.11.09.467897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequestration of LINE-1 in novel cytosolic bodies by MOV10 restricts retrotransposition

Abstract: LINE-1 (L1) are autonomous retroelements that have retained their ability to mobilize. Mechanisms regulating L1 mobility include DNA methylation in somatic cells and the Piwi-interacting RNA pathway in the germline. During pre-implantation stages of mouse embryonic development, however, both pathways are inactivated leading to a critical window necessitating alternate means of L1 regulation. We previously reported an increase in L1 levels in Dicer_KO mouse embryonic stem cells (mESCs). Intriguingly this was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Loss of MOV10 caused upregulation of two L1 families but did not change the overall level of L1 transcripts in mouse testis. In addition, MOV10 sequesters L1 ribonucleoprotein particles in the cytosolic aggregates [55]. Second, MOV10 interacts with L1-encoded ORF2 and recombinant MOV10 blocks reverse transcription in vitro [51].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of MOV10 caused upregulation of two L1 families but did not change the overall level of L1 transcripts in mouse testis. In addition, MOV10 sequesters L1 ribonucleoprotein particles in the cytosolic aggregates [55]. Second, MOV10 interacts with L1-encoded ORF2 and recombinant MOV10 blocks reverse transcription in vitro [51].…”
Section: Discussionmentioning
confidence: 99%
“…We further showed that TUT, and, to a much lesser extent, TUT7 interact in an RNAdependent manner with MOV10, which is a 5 0 ? 3 0 helicase binding to the LINE-1 mRNA 3 0 ends [154] and a known virus and retrotransposon restriction factor [155][156][157][158][159][160][161][162]. In fact, further in vitro biochemical and in vivo cross-linking assays confirmed that MOV10 can traverse along the LINE-1 3' UTR sequence displacing the bound proteins (L1-ORF1p) and likely setting the stage for uridylation [65].…”
Section: In the Cytoplasm: Poly(a) Tails Uridylation Rnp Sequestratio...mentioning
confidence: 96%
“…LINE-1 RNPs aggregate in cytoplasm-forming foci, which I propose calling LINE-1 bodies, often colocalizing with endogenous proteins markers of stress granules, P-bodies or even virus-like particles [48,65,[171][172][173][174]. Recently, sequestration of LINE-1 RNPs in cytoplasmic bodies comprising MOV10 and enhanced by MOV10 overexpression was suggested as a mechanism of LINE-1 retrotransposition restriction in DICER KO mouse ESCs [162]. Another study showed the sequestration of LINE-1 RNPs to stress granules upon HCV infection and linked this with reduced retrotransposition [175].…”
Section: In the Cytoplasm: Poly(a) Tails Uridylation Rnp Sequestratio...mentioning
confidence: 99%
See 2 more Smart Citations